Analysis of Protein Oxidative Modifications in Follicular Fluid from Fertile Women: Natural Versus Stimulated Cycles - Irantzu Pérez-Ruiz; Susana Meijide; María-Luisa Hérnandez; Rosaura Navarro; Zaloa Larreategui; Marcos Ferrando; María-Begoñ; José-Ignaci (MDPI AG, 2018)
Oxidative stress is associated with obstetric complications during ovarian hyperstimulation in women undergoing in vitro fertilization. The follicular fluid contains high levels of proteins, which are the main targets of free radicals. The aim of this work was to determine specific biomarkers of non-enzymatic oxidative modifications of proteins from follicular fluid in vivo, and the effect of ovarian stimulation with gonadotropins on these biomarkers. For this purpose, 27 fertile women underwent both a natural and a stimulated cycle. The biomarkers, glutamic semialdehyde (GSA), aminoadipic semialdehyde (AASA), Nε-(carboxymethyl)lysine (CML), and Nε-(carboxyethyl)lysine (CEL), were measured by gas-liquid chromatography coupled to mass spectrometry. Results showed that follicular fluid contained products of protein modifications by direct metal-catalyzed oxidation (GSA and AASA), glycoxidation (CML and CEL), and lipoxidation (CML). GSA was the most abundant biomarker (91.5%). The levels of CML amounted to 6% of the total lesions and were higher than AASA (1.3%) and CEL (1.2%). In the natural cycle, CEL was significantly lower (p < 0.05) than in the stimulated cycle, suggesting that natural cycles are more protected against protein glycoxidation. These findings are the basis for further research to elucidate the possible relevance of this follicular biomarker of advanced glycation end product in fertility programs.